2014
DOI: 10.1080/09585176.2013.874952
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ views of their assessment practice

Abstract: The main aim of this research was to analyse teachers' views of pupil assessment. The theoretical framework was based on existing literature on advances and challenges of pupil assessment in regard to support for learning, fairness, educational partnership, feedback, and favourable methods. The data were gathered by means of a questionnaire designed for teachers of comprehensive schools. Teachers were first asked to describe a good (right/fair) and a bad (wrong/unfair) case of pupil assessment selected from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 32 publications
(20 reference statements)
0
10
0
9
Order By: Relevance
“…Atjonen (2014) showed that teachers have a positive attitude toward use of different assessment methods, encouraging feedback, an interactive approach, and criteria clarification. But they have negative views about weak implemented assessment, improper assessment methods, degree of stringency, and weak grounds for assessment (27). Dehnavi et al (2004) touched upon the importance of principals' evaluation of the teachers, because the teachers are oversensitive about evaluation, and evaluation has a significant effect on teachers' morale (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atjonen (2014) showed that teachers have a positive attitude toward use of different assessment methods, encouraging feedback, an interactive approach, and criteria clarification. But they have negative views about weak implemented assessment, improper assessment methods, degree of stringency, and weak grounds for assessment (27). Dehnavi et al (2004) touched upon the importance of principals' evaluation of the teachers, because the teachers are oversensitive about evaluation, and evaluation has a significant effect on teachers' morale (19).…”
Section: Discussionmentioning
confidence: 99%
“…In this section, some questions regarding establishing elementary school teachers' union, employing prominent professors for holding educational workshops in the teachers' meetings, the establishment of elementary school teachers 'scientific-cultural associations, inviting officials to respond to teachers' problems in the elementary school teachers' meetings (23-26) Table 1. Seven factors of exhilaration questionnaire of teacher and number of questions in each factors In this section, some questions regarding the teachers' performance evaluation by considering all aspects of their work, taking into account the specific problems of elementary school teachers when evaluating their performance, giving importance to their views as experts when evaluating their performance, evaluating teachers' performance based on objective criteria and promotion of teachers based on a rigorous teacher-evaluation program were raised (19,23,(26)(27)(28)(29).…”
Section: Teachers' Gatheringmentioning
confidence: 99%
“…Dentro de la línea de las concepciones de los docentes cobran especial relevancia las investigaciones que se centran en conocer dichas concepciones acerca de la evaluación (Atjonen, 2014;Brown, 2004;Brown y Hirschfeld, 2008;Brown y Remesal, 2012;Hidalgo y Murillo, 2017;Remesal, 2011;Winterbottom, Brindley, Taber, Fisher, Finney y Riga, 2008). De acuerdo con Prieto (2008), la influencia de las concepciones en la evaluación que llevan a cabo los docentes es clara: las creencias que tiene el profesorado tienen repercusiones directas sobre su práctica evaluativa y éstas en el aprendizaje de los estudiantes.…”
Section: Marco Teóricounclassified
“…Tal y como venimos diciendo, un fructífera y reciente línea de investigación es la que estudia las concepciones sobre el proceso de evaluación del aprendizaje (Atjonen, 2014;Azis, 2012;Brown, 2003, 2004, Brown y Hirschfeld, 2008Brown y Remesal, 2012;Brown, Lake y Matters, 2011;Chen, Morris y Mansour, 2012;Fives y Gill, 2014;Harris y Brown, 2008Winterbottom et al, 2008; entre otros).…”
Section: Las Investigaciones Sobre Concepciones De Evaluación Una Reunclassified